Improving Learning Motivation of Natural-Social Science Learning Through Game-Based Learning Utilising Quartet Cards - Pradita, Ayu Surya; Nisa, Ana Fitrotun; Masjid, Akbar Al; Cahyani, Berliana Henu (Jurnal Pendidikan MIPA, 2024)
Objective: This research aims to determine the effect of using the game-based learning (GBL) model on fostering learning motivation in natural-social sciences (IPAS) learning. The use of the game-based learning model can serve as an alternative in innovative learning activities. Method: The method used in this research is a quasi-experimental method with a quantitative approach. This research uses a one-group pre-test and post-test design. The subjects in this study are 24 third-grade students at SD Negeri 2 Danguran. The data analysis technique used is the "t" test processed using the SPSS 29 application. In the implementation of the research, natural-social science learning used the GBL model with learning media, IPAS quartet cards. Data collection was conducted through the completion of questionnaires that had been tested for validity and reliability. Findings: The significant learning motivation scores of students can be interpreted as the null hypothesis, which states that there is a difference after and before the implementation of the game-based learning is received. The average score of students' responses after the treatment is better than the average score of students' responses before the treatment. Conclusion: Implementing an innovative and interactive learning model for students, specifically through a game-based learning model utilizing IPAS quartet cards, led to this increase.       Keywords: game-based learning, quartet cards, learning motivation, natural-social science. DOI: http://dx.doi.org/10.23960/jpmipa/v25i4.pp1705-1718